Fusiecongres NBPO en NVPD in het NV-huis. Voorzitter Bakker (NBPO, links) luistert naar Bouw (NVPD)
Fusiecongres NBPO en NVPD in het NV-huis. Voorzitter Bakker (NBPO, links) luistert naar Bouw (NVPD).